Analysis of the Effect Good Corporate Governance on Financial Performance Islamic Banking - Amelia, Merry; Ridwansyah, Ridwansyah; Fortuna, Salsabila Mutia (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to investigate the impact of Good Corporate Governance (GCG) on the financial performance of Islamic banking, specifically measured by Return on Equity (ROE) and Return on Assets (ROA). To achieve this objective, a quantitative research approach is employed, utilizing multiple linear regression analysis to assess the relationship between GCG and the financial performance indicators. The GCG variables examined in this study include the size of the board of directors, the Sharia supervisory board, and the board of commissioners. The population for this research consists of Indonesian Islamic commercial banks, with Bank Muamalat Indonesia serving as the primary case study. The data collected spans the years 2018 to 2022, providing a comprehensive view of the bank's performance over this period. The findings of the study indicate that there is no significant evidence to support a strong relationship between sound GCG practices and financial success in terms of ROE and ROA. This suggests that while GCG is essential for overall governance, its direct impact on financial performance may not be as pronounced as anticipated. Additionally, the study acknowledges several limitations, including the focus on a single bank, which may not fully represent the broader Islamic banking sector in Indonesia. The analysis is also constrained by the availability of data and the specific time frame considered, which may affect the generalizability of the results. Future research could expand the sample size and explore additional factors influencing financial performance in Islamic banking, thereby providing a more comprehensive understanding of the dynamics at play